Appropriate technologies for environmental protection in the developing world : selected papers from ERTEP 2007, July 17-19 2007, Ghana, Africa - Yanful, Ernest K (Springer, 2017)
The goal of the book is to discuss environmental policy and present northern and southern technologies and scientific methods that address specific environmental problems affecting humanity in general, but more specifically, people and ecosystems in developing countries. The book contains selected, refereed papers submitted to or presented at the First International Conference on Environmental Research, Technology and Policy held in Accra, Ghana, July 17-19, 2007. The primary goal of the conference was to provide a forum for policy makers, scientists, practitioners, and civil society advocates to discuss grass-root environmental issues, assess efforts by government machinery and identify what communities and corporate entities can do as a social responsibility to mainstream environmental protection for sustainable development. It is acknowledged that environmental research, technology applications and policy implementation have been demonstrated to improve environmental sustainability and protection in several developed economies. The book argues that similar gains can be achieved in developing countries and countries in transition